Overview of Sleep Quality on The Incidence of Hypertension Study: Sys-tematic Literature Review - Liza Virgianti; Nurjazuli Nurjazuli; Bagoes Widjanarko (Eduvest - Journal of Universal Studies, 2025)
This study investigates the impact of poor sleep quality on the incidence and severity of hypertension, drawing from a systematic review of scientific articles published between 2019 and 2024. The review synthesizes findings from various studies sourced from PubMed and Google Scholar using the keywords "Hypertension and Sleep Quality." The results indicate a strong relationship between poor sleep quality and increased blood pressure, particularly in individuals with pre-existing hypertension. Data from 12 core articles highlight that disrupted sleep patterns, including inadequate sleep duration and sleep disturbances, exacerbate hypertension by impairing autonomic nervous system function and increasing cortisol levels. The findings emphasize the need for improving sleep quality as part of hypertension management. This research calls for healthcare systems to integrate sleep quality interventions into hypertension treatment plans to improve outcomes. Future research should focus on exploring the physiological mechanisms linking poor sleep quality with hypertension and the effectiveness of combined interventions, including sleep hygiene education and pharmacological treatments. The study also suggests that targeted interventions considering demographic factors like age and comorbidities may offer more personalized approaches to managing hypertension.